Instability of smoothed particle hydrodynamics applied to Poiseuille flows. (15th September 2018) - Song, Baofang; Pazouki, Arman; Pöschel, Thorsten
Abstract: Smoothed particle hydrodynamics (SPH) has been widely applied to flows with free surface, multi-phase flow, and systems with complex boundary geometry. However, it has been shown that SPH suffers from transverse instability when applied to simple wall-bounded shear flows such as Poiseuille and Couette flows at moderate and high Reynolds number, Re ≳ 1, casting the application of SPH to practical situations into doubt, where the Reynolds number is frequently large. Here, we consider Poiseuille flows for a wide range of Reynolds number and find that the documented instability of SPH can be avoided by using appropriate ratio of smoothing length to particle spacing in combination with a density re-initialization technique, which has not been systematically investigated in simulations of simple shear flows. We also probe the source of the instability and point out the limitations of SPH for wall-bounded shear flows at high Reynolds number.